2013
DOI: 10.1039/c3ra44136a
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and dispersion of polycarbazole wrapped carbon nanotubes

Abstract: Using MM3 force-field simulations in combination with optical measurements, we investigate the morphology and dispersion of a variety of single-walled carbon nanotubes (SWNTs) non-covalently functionalized by carbazole polymers. Our results elucidate that isomer types of poly-carbazoles together with their length govern the morphology of carbazole-SWNT hybrids and, hence, their dispersion and bundling properties. The p-p stacking between the carbazole and the SWNT results in a stable carbazole-SWNT hybrid comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…Semiempirical methods are less computationally expensive than DFT, while giving comparative results for both pristine 68 and functionalized 62 SWCNTs. For instance, AM1 calculations of pristine (7,6) SWCNTs of ∼10 nm in length and capped by hydrogens reproduce the subtle structure and the relevant vibrational effect in the ground and excited state dynamics of SWCNTs that have been confirmed by experimental findings. 51,52,54,69 Based on the AM1 optimized geometries, the single-point electronic structure calculations are performed utilizing 3-21G basis sets using the hybrid density functional B3LYP and the long-range corrected CAM-B3LYP functional, as incorporated into Gaussian-09 software package.…”
Section: ■ Introductionmentioning
confidence: 62%
“…Semiempirical methods are less computationally expensive than DFT, while giving comparative results for both pristine 68 and functionalized 62 SWCNTs. For instance, AM1 calculations of pristine (7,6) SWCNTs of ∼10 nm in length and capped by hydrogens reproduce the subtle structure and the relevant vibrational effect in the ground and excited state dynamics of SWCNTs that have been confirmed by experimental findings. 51,52,54,69 Based on the AM1 optimized geometries, the single-point electronic structure calculations are performed utilizing 3-21G basis sets using the hybrid density functional B3LYP and the long-range corrected CAM-B3LYP functional, as incorporated into Gaussian-09 software package.…”
Section: ■ Introductionmentioning
confidence: 62%
“…By modifying these properties, it is possible to design structures that exhibit some degree of selectivity in their interactions with specific SWNT chiralities . Several conjugated polymer families, including polyfluorenes, polythiophenes, polycarbazoles, and poly(phenyl acetylenes) have been exploited to purify SWNTs, with a preference in many cases toward the dispersion of semiconducting species . A significant challenge with using conjugated polymers is that the majority of these polymers are prepared through step‐growth polymerization techniques, which can lead to significant batch‐to‐batch variability in terms of molecular weight and polydispersity index (PDI) .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been reported about the incorporation of CNTs into a polymer matrix containing carbazole through chemical and electrochemical methods with the goal of combining the unique properties of CNTs and electro-active carbazole. 19,20 Considering the electroactivity of carbazole and the good electrical conductivity of polycarbazole, it has been questioned whether it is possible to achieve a balance of dispersibility and electrical conductivity for CNTs by using an electro-active amphiphilic copolymer containing carbazole units as a dispersant. On one hand, the amphiphilic copolymer could disperse the CNTs efficiently in aqueous solution; on the other hand, the carbazole unit in the amphiphilic copolymer could electropolymerize to form a conducting network, which could enhance the conductivity and accelerate the electron transfer of the CNT hybrid.…”
Section: Introductionmentioning
confidence: 99%